The denticulate ligament: anatomical properties, functional and clinical significance - BAYRİ, YAŞAR (SPRINGER WIEN, 2012)
It is widely believed that the main function of denticulate ligaments (DLs) is to stabilize the spinal cord within the vertebral canal. The aim of this study was to assess the anatomical and histological structure of the DLs and to document any regional differences. Five formalin-fixed adult cadavers were used. The DLs were exposed via the posterior approach, and detailed anatomy and histology of these structures were documented. The main findings were: (1) each DL is composed of a single narrow fibrous strip that extends from the craniovertebral junction to T12, and each also features 18-20 triangular extensions that attach to the dura at their apices; (2) the triangular extensions are smaller and more numerous at the cervical levels, and are larger and less numerous at the thoracic levels; (3) the apices of the extensions attach to the dura via fibrous bands at cervical levels (each band 3-5 mm long) and lower thoracic levels (21-26 mm long), whereas they attach directly to the dura at upper thoracic levels; (4) the narrow fibrous strip of the DL features longitudinally oriented collagen fibers, whereas the triangular extensions are composed of transverse and obliquely oriented collagen fibers. The collagen fibers are thicker and more abundant at the cervical than at the thoracic levels. DL histology and anatomy are strongly correlated with the function of this structure at different spinal levels. It is important to have accurate knowledge about DLs as these structures are relevant for clinical procedures that involve the spinal cord or craniovertebral junction.
Keywords: Anatomy; Denticulate ligament; Function; Histology; Neurosurgery